MAQASHID AL-SYARIAH TENTANG JASA GO-JEK ONLINE PADA WANITA AJNABIYAH DI KABUPATEN BANYUWANGI - Subaidi Subaidi; Subyanto Subyanto (Fakultas Syariah dan Ekonomi Islam, Universitas Ibrahimy, 2025)
Maqashid al-Syariah is a concept that refers to the main objectives of Islamic law which is to maintain the basic interests of individuals and society in building an equitable, harmonious and sustainable life. In the context of Go-Jek online services provided to ajnabiyyah women, becoming a driver even though the passenger is a man. Otherwise women are allowed to become Go-jek online passengers even though the driver is a man.